Modelling the Effect of Electrification on Volcanic Ash Aggregation - Pollastri, Stefano; Rossi, Eduardo; Bonadonna, Costanza; Merrison, Jonathan P. (Frontiers in Earth Science, 2021)
The fine ash released into the atmosphere (particles < 63 m) during explosive volcanic eruptions represents a significant threat for both the ecosystem and many sectors of society. In order to mitigate the associated impact, ash dispersal models need to accurately estimate ash concentration through time and space. Since most fine ash sediments in the form of aggregates, ash dispersal models require a quantitative description of ash aggregation. The physical and chemical processes involved in the collision and sticking of volcanic ash have been extensively studied in the last few decades. Among the different factors affecting volcanic particle aggregation (e.g. turbulence, particle-particle adhesion, presence of liquid and solid water), the charge carried by volcanic particles has been found to play a crucial role. However, Coulomb interactions are not yet taken into account in existing models. In order to fill this gap, we propose a strategy to take charge into account. In particular, we introduce a quantitative model for aggregation of oppositely charged micron- to millimetre-sized objects settling in still air. Our results show that the presence of charge considerably enhances the collision efficiency when one of the colliding objects is very fine (< 20 µm), and that the sticking efficiency is not affected by particle charge if colliding objects are either small enough (< 20 µm) or large enough ( > 200 µm). Besides providing a theoretical framework to quantify the effect of charge, our findings demonstrate that aggregation models that do not account for electrification significantly underestimate the amount of fine ash that sediments in the form of aggregates, leading to an overestimation of the residence time of fine ash in the atmosphere after explosive volcanic eruptions.